THE EFFECTIVENESS OF CRIMINAL LAW ENFORCEMENT AGAINST THE DESTRUCTION OF RUPIAH BANKNOTES IN THE PERSPECTIVE OF LAW NUMBER 7 OF 2011 - Mario Simbolon; Ratu Mawar Kartina (Fakultas Hukum Universitas Swadaya Gunung Jati, 2027)
Background. The state’s effort to safeguard the integrity of the currency as a legal tender as well as a symbol of sovereignty is through the implementation of criminal law against the destruction of the rupiah. Law Number 7 of 2011 on Currency forbids and provides criminal punishments for damaging, cutting, destroying, and/or changing the Rupiah. However, infractions are still routinely committed in practice, especially by marking off money, which is typically viewed as a small act. Aims. This study intends to assess the effectiveness of criminal law enforcement in combating the destruction of rupiah banknotes and the factors that influence it. The research method is empirical juridical, using a qualitative approach to examine the rules of law and their application in the community. Result. The study's findings suggest that law enforcement has not been working at its best. This is affected by poor legal content that does not provide clear limitations, the low priority given to handling by law enforcement officials, and the low level of legal understanding among the people. The fundamental problem is likewise the difficulty of showing the aspect of intentionality. Conclusion. There is a requirement to undertake comprehensive efforts through the improvement of legislative norms, the strengthening of institutional performance, and the improvement of public education. Implementation. Law Enforcement would thus be more effective in preserving the Rupiah's honor as a symbol of the state.